Biodefluorination of Perfluorooctanesulphonate by Ensifer adhaerens M1 - Sharipov Danil; Starikov Sergey; Chetverikov Sergey (HAYATI Journal of Biosciences, 2023)
A strain of bacteria M1, defluorinating perfluorooctanesulfonic acid (PFOS), was isolated from soil taken from the territory for testing fire extinguishing agents. The analysis of cultural, morphological, physiological and biochemical characters, the 16S rRNA gene sequencing allowed us to identify strain M1 as Ensifer adhaerens. The uniquely skill of the isolated strain to utilize PFOS in a mineral liquid medium for 5 days of cultivation was shown. It was found that E. adhaerens M1 transforms perfluorooctanesulfonic acid into perfluoroheptanoic acid, releasing 152 mg/L of free fluoride ions from 1,000 mg/L of PFOS. The data obtained allow us to recommend E. adhaerens M1 as potential treatment agent of the environment from organofluorine compounds.